Barriers and facilitators to promoting evidence uptake in Chinese medicine: a qualitative study in Hong Kong - Charlene Hoi Lam Wong; Jeffrey Van Ho Tse; Per Nilsen; Leonard Ho; Irene Xin Yin Wu; Vincent Chi Ho Chung (BMC, 2021)
Abstract Background In response to the World Health Organization's recommendation, policy makers have been adopting evidence-based healthcare approach to promote the development of traditional, complementary and integrative medicine (TCIM) into Hong Kong's health system. Disseminating synopses of clinical evidence from systematic reviews or randomized trials is regarded as a potentially effective strategy to promote evidence uptake. The study aimed to identify barriers and facilitators to implementing this strategy among Hong Kong Chinese medicine practitioners (CMPs). Methods Twenty-five CMPs aged under 45 years and trained in Hong Kong after reunification with China in 1997 were interviewed individually. Four clinical evidence synopses of randomized trials and systematic reviews on Chinese medicine interventions were presented, and CMPs were asked to comment on their applicability in routine practice. The Consolidated Framework for Implementation Research (CFIR) was applied to guide interview and analysis. Results The barriers included: i) CMPs' perceived difficulties in applying complex evidence in decision-making and ii) inadequate training and limited consultation time. The facilitators were i) availability of publicly accessible and user-friendly synopses, ii) formation of community of evidence-based practice among CMPs with input from key opinion leaders, iii) opportunity for interprofessional collaborations with conventional healthcare providers, and iv) patients' demand for evidence-based clinical advice. Besides, i) CMPs' knowledge and beliefs in evidence-based healthcare approach, ii) presentations of evidence-based information in the synopses, and iii) clinical decision making as influenced by quality of evidence reported acted as both barriers and facilitators. Conclusions This CFIR-based qualitative study investigated how the World Health Organization recommendation of promoting evidence use in routine practice was perceived by CMPs trained in Hong Kong after reunification with China in 1997. Key barriers and facilitators to applying evidence were identified. Such results will inform tailoring of implementation strategies for promoting evidence uptake, in the context of a well-developed health system dominated by conventional medicine.